2020
DOI: 10.1111/resp.13805
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression across the spectrum of idiopathic pulmonary fibrosis: A multicentre study

Abstract: Background and objective: In clinical practice, a working diagnosis of IPF may be performed to provide effective antifibrotic treatment to patients who cannot undergo SLB. In this study, we compared the disease course across IPF diagnostic categories in a real-life clinical setting to clarify the appropriateness of a working diagnosis of IPF and treatment initiation in these patients. Methods: Longitudinal data from IPF patients receiving antifibrotic treatment (pirfenidone or nintedanib) were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While these studies provide compelling data to support the utility of TBLC integration into ILD diagnostic algorithms, the utility of lung biopsies in the diagnosis of IPF is less clear. A retrospective multicentre analysis between 2011 and 2017 showed that more than half of the patients with a possible UIP pattern on HRCT were labelled and treated as IPF with antifibrotic agents, suggesting a general tendency of clinicians avoiding invasive procedures 18 . More importantly, the study showed that patients with a possible UIP pattern on HRCT without histopathological confirmation had similar mortality and disease progression compared to those with a definite diagnosis of IPF.…”
Section: Diagnosis Of Ildmentioning
confidence: 96%
“…While these studies provide compelling data to support the utility of TBLC integration into ILD diagnostic algorithms, the utility of lung biopsies in the diagnosis of IPF is less clear. A retrospective multicentre analysis between 2011 and 2017 showed that more than half of the patients with a possible UIP pattern on HRCT were labelled and treated as IPF with antifibrotic agents, suggesting a general tendency of clinicians avoiding invasive procedures 18 . More importantly, the study showed that patients with a possible UIP pattern on HRCT without histopathological confirmation had similar mortality and disease progression compared to those with a definite diagnosis of IPF.…”
Section: Diagnosis Of Ildmentioning
confidence: 96%
“…Notably, the improvement of survival rate and progression-free survival was observed across different clinical (age, sex, respiratory functional parameters) and/or diagnostic subgroups (confident or working diagnosis) of patients affected with IPF [ 12 , 13 ]. However, no specific trials have been conducted for the evaluation of nintedanib efficacy in patients with familial pulmonary fibrosis (FPF), even though FPF is estimated to represent at least 10% of IPF [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laura M. Glenn, BMed, MD1,2,3 and Tamera J. Corte, BSc (Med), MBBS (Hons), FRACP, PhD1,2,3 1 Interstitial Lung Diseases Unit, Department of Respiratory and Sleep Medicine, Royal Prince Alfred Hospital, Sydney, NSW, Australia; 2 The University of Sydney School of Medicine (Central Clinical School), Sydney, NSW, Australia; 3 NHMRC Centre of Research Excellence in Pulmonary Fibrosis, Sydney, NSW, Australia…”
mentioning
confidence: 99%
“…In a recent publication in Respirology , Sgalla et al . retrospectively compared the rates of mortality and disease progression in 249 IPF patients receiving anti‐fibrotic treatment across three centres in Italy between two diagnostic subgroups: patients with definite UIP on HRCT or SLB and patients with possible UIP on HRCT and no SLB 3 . The major finding of this study was that patients with possible UIP demonstrated similar mortality (log‐rank test P = 0.771) and disease progression (log‐rank test P = 0.139) as compared to patients with UIP on HRCT or SLB.…”
mentioning
confidence: 99%